Safe pregnancy after liver transplantation: Evidence from a multicenter Italian collaborative study. Issue 5 (May 2022) - Sciarrone, Salvatore Stefano; Ferrarese, Alberto; Bizzaro, Debora; Volpato, Sofia; Donato, Francesca Maria; Invernizzi, Federica; Trespidi, Laura; Ramezzana, Ilaria Giuditta; Avolio, Alfonso Wolfango; Nure, Erida; Pascale, Marco Maria; Fagiuoli, Stefano; et al.
Abstract: Background: Women who have undergone liver transplantation (LT) enjoy better health, and possibility of childbearing. However, maternal and graft risks, optimal immunosuppression, and fetal outcome is still to clarify. Aim: Aim of the study was to assess outcomes of pregnancy after LT at national level. Methods: In 2019, under the auspices of the Permanent Transplant Committee of the Italian Association for the Study of the Liver, a multicenter survey including 14 Italian LT-centers was conducted aiming at evaluating the outcomes of recipients and newborns, and graft injury/function parameters during pregnancy in LT-recipients. Results: Sixty-two pregnancies occurred in 60 LT-recipients between 1990 and 2018. Median age at the time of pregnancy was 31-years and median time from transplantation to conception was 8-years. During pregnancy, 4 recipients experienced maternal complications with hospital admission. Live-birth-rate was 100%. Prematurity occurred in 25/62 newborns, and 8/62 newborns had low-birth-weight. Cyclosporine was used in 16 and Tacrolimus in 37 pregnancies, with no different maternal or newborn outcomes. Low-birth-weight was correlated to high values of AST, ALT and GGT. Conclusion: Pregnancy after LT has good outcome; however, maternal complications and prematurity may occur. Compliance with the immunosuppression is fundamental to ensure the stability of graft function and prevent graft-deterioration.